Disparities in ovarian cancer survival at the only NCI-designated cancer center in Kansas - Petersen, Shariska (Am J Surg, 2020)
BACKGROUND: This study examined the impact of geographic distance on survival outcomes for patients receiving treatment for ovarian cancer at the only NCI-designated cancer center (NCI-CC) in Kansas. METHODS: We identified ovarian cancer patients treated at the University of Kansas Cancer Center between 2010 and 2015. Demographic factors and clinical characteristics were abstracted. The main outcome measure was overall survival according to geographic distance from the institution. Kaplan Meier survival curves and Cox proportional hazard models were generated using SAS v9.4. RESULTS: 220 patients were identified. Survival analysis based on distance from the institution demonstrated that patients who lived ≤10 miles from the institution had worse overall survival (p = 0.0207) and were more likely to have suboptimal cytoreductive surgery (p = 0.0276). Lower estimated median income was also associated with a 1.54 increased risk of death, 95% CI (1.031–2.292), p = 0.0347. CONCLUSIONS: We determined that ovarian cancer survival disparities exist in our patient population. Lower rates of optimal cytoreductive surgery has been identified as a possible driver of poor prognosis for patients who lived in proximity to our institution.